Kesetaraan Suami-Isteri dalam Perkawinan Adat To Kulawi Ditinjau dari Perspektif Hak Asasi Manusia - Lasatu, Asri; Jubair, Jubair; Insarullah, Insarullah; Fattah, Virgayani; Friskanov. S, Irzha (Faculty of Law, Institut Ilmu Sosial dan Bisnis Andi Sapada., 2023)
The Government of Indonesia is committed to advancing social and political rights through various means, by protecting, respecting and fulfilling the civil and political rights of every citizen. Likewise with the Convention on the Elimination of All Forms of Discrimination Against Women which has been ratified. These two aspects are interesting things to study, including: how are the laws related to these matters made and how are these laws complied with?—remembering that Indonesia is a large country consisting of many islands and different customs—Discrimination against women often occurs between married couples in marriage. This study aims to determine the responsibilities of husband and wife in marriage from the perspective of human rights and Kulawi customary law. The results of the study illustrate that the responsibilities of husband and wife in marriage in the perspective of Kulawi customary law are in line with the International Covenant on Civil and Political Rights and the International Convention on Elimination of All Forms of Discrimination Against Woman. Women in the view of Kulawi customary law are given protection both legally, economically and socially. ___ Referensi Buku dengan penulis: Ali, A. (2009). Menguak Teori Hukum (Legal Theory) dan Teori Peradilan (Jurisprudence); Termasuk Interpretasi Undang-Undang. Jakarta: Kencana. Davidson, Scott. (1994). Hak Asasi Manusia: Sejarah, Teori dan Praktek dalam Pergaulan Internasional. Jakarta: Pustaka Utama Grafiti. Faisal, Sanapiah. (2005). Format-Format Penelitian Sosial: Dasar-Dasar dan Aplikasi. Jakarta: Rajagrafindo Perkasa. Irwansyah. (2020). Penelitian Hukum, Pilihan Metode dan Praktik Penulisan Artikel. Yogyakarta: Mirra Buana Media. Artikel jurnal: Kalalo, J. J. J., & Irwansyah, I. (2019). Dikotomi Politik Hukum Nasional dengan Politik Hukum Adat di Daerah Perbatasan. Amsir Law Journal, 1(1), 22-35. Kania, D. (2015). Hak Asasi Perempuan Dalam Peraturan Perundang-Undangan di Indonesia. Jurnal Konstitusi, 12(4), 716-734. Karim, K., & Syahril, M. A. F. (2021). Simplifikasi Pembagian Harta Gono-Gini Akibat Perceraian. Jurnal Litigasi Amsir, 9(1), 1-12. Laitupa, S., & Kartika, E. D. (2022). Eksistensi Hukum Internasional terhadap Hukum Nasional dalam Pembuatan Perjanjian Internasional. Amsir Law Journal, 3(2), 63-75. Miqat, N., & Bakhtiar, H. S. (2017). Harmonization of Uang Panaik as Customary Term in Bugis-Makassar Ethnic Group and Dowry in Indonesian Marriage System. JL Pol'y & Globalization, 67, 41. Miqat, N., Nur, R., Fattah, V., Sulilawati, S., & Purnamasari, I. (2021). Local Wisdom of Customary Law Community to Realize Food Sovereignty in Central Sulawesi. Jambura Law Review, 3(2), 277-294. Rahayu, N. (2012). Kesetaraan Gender dalam Aturan Hukum dan Implementasinya di Indonesia Gender Equality in the Rule of Law in Indonesian and Implementation. Jurnal Legislasi Indonesia, 9(1), 15-32. Rahayu, R. (2021). Perlindungan Hak Asasi Manusia Perempuan terhadap Kasus Kekerasan dalam Rumah Tangga di Indonesia dalam Perspektif Hukum Internasional. Jurnal HAM, 12(2), 261-272. Rakia, A. S. R., & Hidaya, W. A. (2022). Aspek Feminist Legal Theory dalam Peraturan Perundang-undangan di Indonesia. Amsir Law Journal, 4(1), 69-88. Syarifuddin, J. S., Karim, K., & Suardi, S. (2021). Legum Studia Penyelesaian Sengketa Harta Bersama. Jurnal Litigasi Amsir, 9(1), 70-76. Ulil, A., Lazuardi, S., & Putri, D. C. (2020). Arsitektur Penerapan Omnibus Law melalui Transplantasi Hukum Nasional Pembentukan Undang-Undang. Jurnal Ilmiah Kebijakan Hukum, 14(1), 1-18.